The Effect of Compensation and Work Environment on the Employee of Linting Section Performance at Dua Dewi Cigarette Factory in Kediri - Hellenna Soraya; Desi Kristanti; Duwi Riningsih (Pusat Riset dan Inovasi Nasional, 2024)
Human resources play a crucial role in achieving organizational goals, where compensation and the work environment are the main factors influencing employee performance. This study aims to determine the influence of compensation and work environment on the performance of employees in the linting section at Dua Dewi Cigarette Factory Kediri. The research approach used is associative quantitative, with a survey method involving questionnaires distributed to 40 employees as the sample. Data analysis was conducted using multiple linear regression with the assistance of SPSS 25. The results of the t-test showed that both compensation and work environment had a significant influence on performance partially, with significance values of 0.020 and 0.002, respectively. The F-test result showed a significance value of 0.000, indicating that compensation and work environment simultaneously affect employee performance. The work environment was found to be the most dominant variable.